EP680 Impact of Pregnancy on the risk of breast and ovarian cancer in BRCA1 and BRCA2 mutation carriers. (1st November 2019) - Russo, M; Corvetto, E; Fais, M; Candotti, G; Locati, V; Proto, A; Angioni, S; Carcassi, C; Mais, V; Peiretti, M
Abstract : Introduction/Background: BRCA 1 and 2 mutated women have a 40–85% lifetime risk of developing breast cancer (BC) and 16–64% risk of ovarian cancer (OC). Literature data evaluating the role of pregnancies on risk of BC and OC in BRCA mutated patients are controversial. The objective of the present study is to evaluate the impact of pregnancy on cancer risk in a cohort of BRCA1/2 mutated patients. Methodology: This is a retrospective study, conducted on a sample of 106 female patients, 83 (78%) with BRCA 1 mutation and 23 (22%) BRCA 2, involved in a follow-up program of two different divisions of the University of Cagliari. We evaluated the number of BC and OC and the age of cancer diagnosis correlating to the number of pregnancies. Results: Of 106 patients, 39 (36, 8%) patients did´t have diagnosis of cancer and 67 (63, 2%) developed cancer: 48 BC, 12 OC and 7 both. Thirthy-nine (36, 8%) women didn´t have pregnancy, 21 (19, 8%) had one pregnancy, 27 (25, 4%) had two pregnancies and 19 (17, 9%) more than two pregnancies. The median age at the cancer diagnosis was 43, 3 years (range 19–69 years). We found a significative difference on the age of cancer diagnosis in patients with two or more pregnancies (p-value <0, 001). Patients with no or one pregnancy developed cancer at a median age of 38, 3 years (range 19–59 ys), patients with two or more pregnancies at 49, 5 ys (29–69 ys). Conclusion: Our results seems to suggest a protective effect of pregnancy on the development of cancer in BRCA mutated women. Data show that two or more pregnancies significantly delay the development breast and ovarian cancer. Disclosure: Nothing to disclose.